Research advances of CCR2/MCP-1 and kidney diseases - Shen Yan-jie; Yan Li-li; Ren Zhen-hua; Lu Ling; Zhang Qin (Linchuang shenzangbing zazhi)
As a major receptor of monocyte chemotactic protein-1（MCP-1）,CC chemokine receptor 2（CCR2）can specifically conjugate to MCP-1,transfer signals into cytoplasm, mediate the chemotaxis and activation of monocytes and macrophages and promote the occurrence and development of inflammation.Previous studies have shown that CCR2/MCP-1 were involved in the development of many kidney diseases.This review summarized the recent research advances of CCR2/MCP-1 and kidney disease.